KOMITMEN ORGANISASI DAN PRODUKTIVITAS KERJA DITINJAU DARI GAYA KEPEMIMPINAN INTRINSIK: SUATU KAJIAN SPIRITUALITAS DAN AGAMA DI TEMPAT KERJA - Sitti Syawaliyah Gismin; Ahmad Yasser Mansyur (Jurnal Psikologi TALENTA, 2018)
The discourse of leadership style in this study is part of the concept of spiritualias and religion in the workplace (spirituality and religion in the workplace-SRW) which can be an important study material for developing leadership theories to improve organizational outcomes in the midst of global environmental change. This study aims to examine the effect of three leadership styles namely prophetic leadership, spiritual leadership and transformational leadership on organizational commitment and work productivity in the organization. A total of 216 respondents from three organizations (business, public and non-profit) based on Islam in the Makassar-Indonesia region were involved in this study. Five measuring tools were used to gather information about the variables studied, namely the Organizational Commitment Questionnaire, Productivity, the SLT Survey Questions, the Multifactor Leadership Questionnaire and L-Prophetic. Parametric inferential statistics in the form of multiple regression analysis and one-way ANOVA are used to reveal the results of each of the variables studied. The results of the study show that there are joint effects of three leadership styles on organizational commitment and work productivity. Of the three leadership styles, prophetic leadership style and dominant spiritual leadership influence organizational commitment and work productivity. In addition, the three leadership styles have the same dominance (existence) in nonprofit organizations. The results of this study enriched the concept of sharia-based prophetic leadership style that was useful for the development of SRW studies, Islamic Psychology and supported the spirit of Indigenous Psychology.